Interdisipliner : Paradigma Kajian Ilmu Sosial-Humaniora dalam Studi Agama Islam - Nakiyah, Lutfiyatun (FIRDAUS: Jurnal Keislaman, Pemikiran Islam, dan Living Qur'an, 2024)
The interdisciplinary paradigm offers an approach to Islamic religion with a broader scientific insight, namely from a social-humanities perspective. This allows Islamic religious discourse to develop in relevant stages and line with the empirical postulates of knowledge and historical social phenomena. Comprehensive Islamic discourse insight and sholihun likulli zaman are the essences of Islamic teachings. Through an interdisciplinary paradigm, spaces for ijtihad of thought are opened in the process of enriching the development of Islamic studies literature. The interdisciplinary paradigm also allows dialectical space to be formed due to the meeting of various scientific disciplines juxtaposed with the dialectic of Islamic studies literature which is also deeply rooted. Therefore, it will reveal a more comprehensive understanding of Islam regarding the essence of Islamic teachings. This relationship has a clarifying, complementary, affirmative, corrective, verification, and transformative pattern as well as an integrative-interconnective pattern.